Memoir as a form of auto-ethnographic research for exploring the practice of transnational higher education in China - Scott, Joy Denise (Routledge, 2014)
In this paper, I argue that memoir, as a form of auto-ethnographic research, is an appropriate method for exploring the complexities and singularities in the practice of western educational practitioners who are immersed in the social reality of offshore higher education institutions, such as those in Mainland China. I illustrate this proposition by showing how my own use of memoir is guided by a need to interrogate the unique experiences of my past life as 'the foreigner', 'the special one', 'the imported expert' and 'the cultural outsider', in order to lay bare the complexity of what it means to work and live in China as a foreign teacher and be recognised as different. I am interested in the notion of foreignness, and the ambiguities that arise when one operates as a teacher in a foreign culture, with a misguided and naïve understanding of one's own specialness as the foreign expert. My research methodology is based on critically reflective writing that acknowledges the multiplicity of historical, cultural and social differences, and the uniqueness of all individuals, whilst recognising that difference, at its heart, is a matter of relationship(s). This form of writing as educational research makes it possible to challenge some of the generalisations western scholars inadvertently make when writing about their teaching experiences in China.